Actual problems of contrastive grammar in the focus of pragmalinguistics - Kovtun, Oksana (Studia Rossica Posnaniensia, 2022)
The term contrastive grammar is still ambiguous. In this paper we trace the unjustified synonymy of terms (confrontative grammar, comparative grammar, contrastive grammar) which lead to controversy among linguists and we attempt to introduce appropriate clarifications to explain the phenomenon. We can state that this linguistic direction is quite new, and its metalanguage is still in the process of development and formation. When studying contrastive grammar in the modern scientific functional-communicative paradigm, the focus of attention is directed to the issues of pragmalinguistics, that is the research, in addition to the actual meanings, of the semantics of linguistic units for designating objects of the environment, also the speech-thinking activity of speakers who use these units and listeners who interpret them; the possible situations of their application; the study of “language in context”; language research, taking into account the goal that is planned to be achieved in the communication process; the wide multidimensionality of the interpretation of the statement; the study of interactive means, taking into account grammatical meanings. The main category of pragmalinguistics is the category of evaluation, and therefore, the issue of contrastive grammar and contrastive description of languages is important to consider in the focus of the paradigm of the category of evaluation; in particular, this concerns the manifestation of each grammatical category.